FATWA DALAM SEJARAH POLITIK IRAN - Sofi Mubarok (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2015)
Recently, the study of political Islam are generally still deals with the debate about the most ideal political system which should apply. Some choose to discuss on how the implementation of the Islamic system in modern society is relatively more pluralist and secular. Therefore, not to get hung up on a similar discussion, the author is interested in reviewing one of the state which experience has managed to implement a system of political Islam in this modern era, namely Iran. With the political system of velayat al-faqih who interpreted from the perspective of Shiaideology as the country’s main imamiyah, Iran deserves further examined particularly associated several implementations of Islamic concepts that have been instituted in such a way in the political system. The author sees a one political concept that has the highest authority in Iran’s political system is at once part of the concept of religion isinteresting when and discussed. The concept is a fatwa which previously only was one topic of discussion in the study of jurisprudence, not affecting politics at all. Then, at this time, the treatise the author wanted to expose in a dialectical-historical account of how the emergence of the fatwa as an important part of the political system in Iran.Keywords: Iran, the shi’i al-Imamiyah, velayat faqih, fatwa, rahbar